Case Report: Triple Primary Malignant Tumors of the Esophagus, Stomach, and Colon in a Patient With Genetic Analysis - Zhan, Xiaoli; He, Lingzhe; Song, Kai; Cao, Shuliang; Meng, Erhong; Wang, Yuedong (Frontiers in Genetics, 2021)
The incidence of multiple primary malignant tumors (MPMTs) has increased greatly with the progress of tumor diagnosis and therapy technology. However, triple primary cancer is still very rare, and its genetic change is not clear yet. This case report described a 70-year-old Chinese male patient with triple primary cancers of the esophagus, stomach and right-sided colon. Pathological examination confirmed that each malignant tumor developed independently. Next-generation sequencing (NGS) using a 599-gene panel revealed five TP53 mutations in three tumor tissues. These variations might contribute to development of the triple primary malignant tumors in the patient. The patient underwent laparoscopic feeding jejunostomy and postoperative radiotherapy for synchronous esophageal and gastric carcinomas. Then, he underwent laparoscopic-assisted resection of right-sided colonic cancer and lysis of abdominal adhesions. By the time of submitting this manuscript, the patient had been well and no sign of recurrence or metastasis had been observed. To the best of our knowledge, this case is the first one to clarify the genetic abnormalities of triple primary cancers of esophagus, stomach and colon in a Chinese patient. It may contribute to understanding the molecular pathogenesis of multiple primary digestive malignancies and providing valuable treatment strategies for the similar patients in the future.